Gums and stabilisers for the food industry 10 - Williams, Peter A.; Phillips, Glyn O. (Special publication (Royal Society of Chemistry (Great Britain)), 2000)
The tenth volume of "Gums and Stabilisers for the Food Industry" provides an up-to-date account of the latest research developments in the characterisation, properties and applications of polysaccharides and proteins used in food